Evaluation of Subjective Sleep Disturbances in Cancer Patients: A Cross-Sectional Study in a Radiotherapy Department - Wang, Jun; Zhou, Bei-Yun; Lian, Chen-Lu; Zhou, Ping; Lin, Hui-Juan; Wu, San-Gang (Frontiers in Psychiatry, 2021)
Background: The factors associated with sleep disturbances in cancer patients remains unclear. This study aimed to explore the prevalence of sleep disorders and predictors associated with sleep disturbance in cancer patients from a radiotherapy department. Methods: Patients with cancers were recruited before the start of radiotherapy from our institution between January 2019 and February 2020. Pittsburgh Sleep Quality Index (PSQI) scale was used to assess sleep quality. Descriptive statistics, Chi-square test, and multivariate logistic regression analysis were used to conduct statistical analysis. Results: A total of 330 eligible patients were included. Of them, 38.3% (n=127) had the globe PSQI score >7, indicating that they suffered from sleep disorders. Patients with lung cancer (45.2%) were more likely to suffer from sleep disturbance, followed by cervical cancer (43.8%), nasopharyngeal carcinoma (41.7%), esophageal cancer (41.5%), breast cancer (37.7%), and colorectal cancer (30%). With regarding the PSQI components, the mean sleep duration was 8 hours, 20.3% (n=67) of them reported poor subjective sleep quality, 6.1% (n=20) needed medication to improve sleep, and 53.6% (n=177) suffered daytime dysfunction. Multivariate logistic regression models showed body mass index (BMI) ≥20kg/m2 (odds ratio [OR] 0.599, 95% confidence interval [CI] 0.329-0.948, P=0.031) and the receipt of surgery (OR 0.507, 95% CI 0.258-0.996, P=0.048) were the significant favorable predictors for sleep disturbance, while age, gender, marital status, education level, comorbidity, metastasis status, diagnostic status, and cancer type were not significantly associated with sleep disturbance. Conclusions: Approximately 40% of the cancer patients suffer from sleep disturbance before the start of radiotherapy. Patients with BMI ≥20kg/m2 and receiving surgery are less likely to develop sleep disturbance in comparison with others.